Equatorial range limits of an intertidal ectotherm are more linked to water than air temperature. (1st June 2016) - Seabra, Rui; Wethey, David S.; Santos, António M.; Gomes, Filipa; Lima, Fernando P.
Abstract: As climate change is expected to impose increasing thermal stress on intertidal organisms, understanding the mechanisms by which body temperatures translate into major biogeographic patterns is of paramount importance. We exposed individuals of the limpet Patella vulgata Linnaeus, 1758, to realistic experimental treatments aimed at disentangling the contribution of water and air temperature for the buildup of thermal stress. Treatments were designed based on temperature data collected at the microhabitat level, from 15 shores along the Atlantic European coast spanning nearly 20° of latitude. Cardiac activity data indicated that thermal stress levels in P. vulgata are directly linked to elevated water temperature, while high air temperature is only stressful if water temperature is also high. In addition, the analysis of the link between population densities and thermal regimes at the studied locations suggests that the occurrence of elevated water temperature may represent a threshold P. vulgata is unable to tolerate. By combining projected temperatures with the temperature threshold identified, we show that climate change will likely result in the westward expansion of the historical distribution gap in the Bay of Biscay (southwest France), and northward contraction of the southern range limit in south Portugal. These findings suggest that even a minor relaxing of the upwelling off northwest Iberia could lead to a dramatic increase in thermal stress, with major consequences for the structure and functioning of the intertidal communities along Iberian rocky shores.